2007
DOI: 10.2174/187152507779315813
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Thrombospondins in Healing Myocardial Infarcts

Abstract: The five current members of the thrombospondin (TSP) family can be divided in two subgroups according to their molecular architecture. TSP-1 and -2 (subgroup A) are trimeric matricellular proteins that do not contribute directly to tissue integrity, but influence cell function by modulating cell-matrix interactions, whereas TSP-3, -4 and -5 (subgroup B) are pentameric proteins. TSP-1 and TSP-2 are markedly induced in healing wounds and may regulate cellular responses important for tissue repair. TSP-1 is a cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…Our findings suggested that the selective endogenous expression of TSP-1 in the infarct border zone may protect the non-infarcted myocardium from inflammatory cell infiltration and fibrotic remodeling. Several distinct TSP-1-mediated actions may be responsible for its protective effects [332]. First, enhanced TGF-β activation in the border zone may locally suppress inflammatory mediator synthesis.…”
Section: The Infarct Border Zone As a Barrier Preventing Expansion Ofmentioning
confidence: 99%
“…Our findings suggested that the selective endogenous expression of TSP-1 in the infarct border zone may protect the non-infarcted myocardium from inflammatory cell infiltration and fibrotic remodeling. Several distinct TSP-1-mediated actions may be responsible for its protective effects [332]. First, enhanced TGF-β activation in the border zone may locally suppress inflammatory mediator synthesis.…”
Section: The Infarct Border Zone As a Barrier Preventing Expansion Ofmentioning
confidence: 99%
“…Therefore, it is no surprise that CD44, which is involved in the ECM-receptor interaction, was found to be downregulated in the current study. Chatila et al (38) also found that certain compositions of the infarct border zone may slow down left ventricular remodeling by suppressing inflammation. In the current study, GO terms enriched by downregulated genes were mainly associated with the stimulus and immune response.…”
Section: Genementioning
confidence: 96%
“…For example, low-density lipoprotein receptor-related protein (LRP) is a versatile scavenger and signaling receptor that binds multiple unrelated ligands and influences a wide variety of biological processes (reviewed by Lillis et al [58]). Since TIMP1 and -2, either alone or complexed with proMMP-2 or -9, respectively, can interact with LRP, it will be of particular interest to investigate whether LRP represents (i) a 'mitogenic' receptor for TIMPs; as it is the 'motogenic' receptor for plasminogen activator inhibitor-1 [59], and/ [58,60,61]. LRP is able to bind thrombospondin-1 and -2, two matricellular proteins that seem to be crucial regulators of the cardiac integrity necessary for the myocardium to cope with increased loading or ischemic stress [60,61].…”
Section: Exploring Receptor-mediated Pathways and Processes In Cardiamentioning
confidence: 99%
“…Since TIMP1 and -2, either alone or complexed with proMMP-2 or -9, respectively, can interact with LRP, it will be of particular interest to investigate whether LRP represents (i) a 'mitogenic' receptor for TIMPs; as it is the 'motogenic' receptor for plasminogen activator inhibitor-1 [59], and/ [58,60,61]. LRP is able to bind thrombospondin-1 and -2, two matricellular proteins that seem to be crucial regulators of the cardiac integrity necessary for the myocardium to cope with increased loading or ischemic stress [60,61]. Interestingly, the proMMP-2/TIMP-2/thrombospondin-triplex can be scavenged via LRP-mediated endocytosis, regulating the levels of both MMP-2 and TIMP-2 in the extracellular cardiac matrix.…”
Section: Exploring Receptor-mediated Pathways and Processes In Cardiamentioning
confidence: 99%